2013
DOI: 10.1016/j.rmed.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The eXpeRience registry: The ‘real-world’ effectiveness of omalizumab in allergic asthma

Abstract: Omalizumab has demonstrated therapeutic benefits in controlled clinical trials. Evaluation of outcomes in real-world clinical practice is needed to provide a complete understanding of the benefits of omalizumab treatment. eXpeRience was a 2-year, international, single-arm, open-label, observational registry that evaluated real-world effectiveness, safety and use of omalizumab therapy in 943 patients with uncontrolled persistent allergic asthma. Effectiveness variables (physician's Global Evaluation of Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
182
2
22

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(235 citation statements)
references
References 32 publications
29
182
2
22
Order By: Relevance
“…Supporting the results from clinical studies, real-world studies conducted in various European countries also reported improvement in asthma control and quality of life of patients after treatment with omalizumab [9][10][11][12]. To strengthen the evidence for omalizumab, a 2-year, global, post-marketing observational registry (eXpeRience) was conducted [13,14].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Supporting the results from clinical studies, real-world studies conducted in various European countries also reported improvement in asthma control and quality of life of patients after treatment with omalizumab [9][10][11][12]. To strengthen the evidence for omalizumab, a 2-year, global, post-marketing observational registry (eXpeRience) was conducted [13,14].…”
Section: Introductionmentioning
confidence: 88%
“…Patients were followed up for 2 years after initiation of omalizumab treatment and data were collected for analysis at week 16 ±1 week, and months 8, 12, 18, and 24. Data reported in this analysis include patient response to therapy (as determined by physician's global evaluation of treatment effectiveness (GETE)), lung function (FEV 1 % predicted and peak expiratory flow (PEF)), clinical symptoms (day-and night-time symptoms), use of rescue medication, use of oral and inhaled corticosteroids, number of clinically significant and severe asthma exacerbations, Asthma Control Test (ACT), patients' health-related quality of life (mini-Asthma Quality of Life Questionnaire (mini-AQLQ)), medical healthcare resource use (hospitalisations, emergency room (ER) visits or unscheduled doctor visits or interventions), number of missed days of work/school, serious adverse events (SAEs) and deaths [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…(возраст 6-17 лет, n = 97) [данные не опу-бликованы]; результатов РКИ IA-05EUP (европейская популяция детей в возрасте 6-11 лет, группа омализу-маба -n = 421, группа плацебо -n = 192) [8]; резуль-татов проспективного наблюдательного исследования eXpeRience [12]. Следует отметить, что РКИ IA-05EUP на данный момент является единственным, в котором исследовался эффект омализумаба исключительно в дет-ской популяции [8].…”
Section: исходные данныеunclassified
“…Марковские переходы стандартной терапии с добав-лением омализумаба экстраполированы путем примене-ния к марковским переходам для стандартной терапии известных клинических эффектов омализумаба, описан-ных выше [8,12,13].…”
Section: марковские переходы марковские переходы для стандартной терапииunclassified
See 1 more Smart Citation